Computer Communication, Networking and Internet Security Proceedings of IC3T 2016 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Raju, K. Srujan; Janakiramaiah, B.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book is a compilation of high-quality scientific papers presented at the 3rd International Conference on Computer & Communication Technologies (IC3T 2016). The individual papers address cutting-edge technologies and applications of soft computing, artificial intelligence and communication. In addition, a variety of further topics are discussed, which include data mining, machine intelligence, fuzzy computing, sensor networks, signal and image processing, human-computer interaction, web intelligence, etc. As such, it offers readers a valuable and unique resource.
Internet of Things & Wireless Physical Layer Security: A Survey -- Approach Towards increasing efficiency of communication protocol in wireless sensor network using modified routing protocol -- Privacy Preservation in Cloud Computing with Double Encryption Method -- A Machine learning based approach for Opinion Mining on Social Network Data -- Congestion Control Mechanism for Real Time Traffic in Mobile Adhoc Networks -- Correction of Ocular Artifacts from EEG by DWT with an Improved Thresholding -- EGRP: Enhanced Geographical Routing protocol for Vehicular Adhoc Networks -- PAPR Performance Analysis of Unitary transforms in SLM-OFDM for WLAN 802.11a Mobile terminals -- Optimal Sensing Time allocation for Energy Efficient Data Transmission in Amplify-Forward Cognitive Relay Assisted Network -- Data Privacy in Online Shopping -- Design and Performance of Resonant Spacing Linear Patch Array with Quarter wave transformer feed Network for Wireless Applications -- Performance analysis of PUEA and SSDF attacks in Cognitive Radio Networks -- Design of a 3.4 GHz Wide-Tuning-Range VCO in 0.18 µm CMOS -- A New Iterative Hybrid Edge Technique Using Image Mosaic -- Performance of Optimized Reversible Vedic Multipliers -- Improved In-System Debugging of High Level Synthesis Generated FPGA Circuits -- Congestion Control Mechanism for Real Time Traffic in Mobile Adhoc Networks -- Impact of Facebookâ€™s Check-in Feature on Users of Social Networking Sites -- A Novel Congestion Control Scheme in VANET.
Keywords: Telecommunication; Data protection; Computational intelligence; Communications Engineering, Networks; Data and Information Security; Computational Intelligence